Collective Bargaining Systems in Six Latin American Countries: Degrees of Autonomy and Decentralization (Argentina, Brazil, Chile, Mexico, Peru, and Uruguay) - Lesley O'Connell (Inter-American Development Bank, Office of the Chief Economist, 1999)
The transition to a market driven development strategy in Latin America for more than a decade has redefined business strategies and reshaped the state`s traditional role as guarantor of employment, stability, and protection. These changes, plus the move to create more flexible labor markets in some countries, have lead to the elimination or reduction of legislated employment protections and benefits, creating space for unions to enlarge their role in collective bargaining.
Keywords: 330; Tarifverhandlungen; Argentinien; Brasilien; Chile; Mexiko; Peru; Uruguay